Ochrona różnorodności biologicznej w systemach certyfikacji FSC i PEFC a prawna ochrona przyrody w Polsce - Referowska-Chodak, Ewa (Leśne Prace Badawcze, 2010)
This paper gives an analysis of documents related to the FSC and PEFC certification systems, which are in force in Poland, in the context of international and national nature protection law. The following questions have been considered: the knowledge of this law, the ability to recognise endangered species, their cataloguing and monitoring, the presence of various nature protection forms, the protection of ecological corridors and societal participation in nature protection. The FSC and PEFC certification systems both refer to these subjects on a large scale, but with different precision and restrictiveness. The good functioning of certification systems requires the simultaneous development of scientific research and ecological education throughout society.